Efficacy of COVID-19 control measures on post-vaccination outbreak in Italian Long Term Care Facilities: implications for policies - Malara, Alba; Noale, Marianna; Trevisan, Caterina; Abbatecola, Angela Marie; Borselli, Gilda; Cafariello, Carmine; Gareri, Pietro; Fumagalli, Stefano; Mossello, Enrico; Volpato, Stefano; Monzani, Fabio; Coin, Alessandra; et al. (Frontiers in Public Health, 2023)
Background: Numerous individual and organizational factors can influence the spread of SARS-CoV-2 infection in Long Term Care Facilities (LTCFs). A range of outbreak control measures are still implemented in most facilities involving administrations, staff, residents and their families. This study aims to evaluate which measure could influence the transmission of SARS-CoV-2 infection among residents during the period March 2021-June 2022. Methods: We enrolled 3272 residents aged ≥60 years. The outbreak control measures adopted to prevent or manage the infection included entry regulation measures, contact-regulating measures, and virological surveillance of residents and staff. The association between LTCFs’ and participants’ characteristics, and new cases of COVID-19 infections was analyzed using multilevel logistic regression models. Results: In 33.8% of the facilities 261 cases of SARS-CoV-2 infection were reported. Among the characteristics of the participants, gender and age were not associated with SARS-CoV-2 infection, while having received the vaccine booster dose was a protective factor against infection (Odds Ratio (OR)=0.34, 95% Confidence Interval (CI) 0.12-0.99, p=0.048). On the other hand, the implementation of protected areas for family visits was associated with a significant reduction of the probability of infections (OR=0.18, 95% CI 0.03-0.98, p=0.047). Overall, about 66% of the variability in the probability of SARS-CoV-2 infection during the period may be attributable to characteristics of facility structures and 34% to characteristics of the participants. Conclusions: These data showed that the vaccination booster doses and family visit restriction-control are still needed to make the LTCFs safer versus SARS-CoV-2 infection.